PERANCANGAN SISTEM APLIKASI KITE IKM DI DIREKTORAT JENDERAL BEA DAN CUKAI BERBASIS JAVAFX - Sharyanto Sharyanto; Rizki Saputra Oni (STIKOM CKI, 2018)
Small and medium industries, have a strategic role in achieving national goals. In general, the problems inherent in small and medium industries are related to five things, namely capital, marketing / competition, technology, management, and human resources. To be able to survive IKM must have a good product. In order to optimize national export realization, the Directorate of Customs and Excise Facilities initiates a new type of facility in the Export Destination Import Facility (FITE), namely the IKM KITE. The IKM KITE facility is an exemption from Import Duty and Value Added Tax or Value Added Tax and Sales Tax on Luxury Goods payable not collected on imports and / or import of Goods and / or Materials to be Processed, Assembled, or Installed on other goods for export purposes and / or Submission of IKM Production.